2012
DOI: 10.4321/s1578-84232012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Estilo interpersonal controlador del entrenador, frustración de las necesidades psicológicas básicas, y burnout en futbolistas infantiles

Abstract: Resumen: En el presente trabajo, basado en la Teoría de las Necesidades Psicológicas Básicas (BPNT; Deci y , se puso a prueba un modelo con la siguiente secuencia: Estilo interpersonal controlador del entrenador Þ Frustración de las necesidades psicológicas básicas Þ Burnout. Participaron 725 futbolistas varones de la categoría infantil con edades comprendidas entre los 11 y los 13 años (M = 12.6; DT = .54) que completaron los instrumentos que evaluaban las variables de interés. Los resultados del análisis de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0
26

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 1 publication
8
16
0
26
Order By: Relevance
“…No significant relationships emerged when analyzing the data at the team level, whereas at the individual level, all the hypothesized relationships were significant. The results obtained at the team level disagree with the BPNT postulates (Ryan & Deci, ), but results at the individual level are in accordance with the postulates of the theory as well as with previous research at the individual between‐person level where the needs were analyzed separately (Castillo et al., ) or together (e.g., Bartholomew et al., ; Balaguer et al., ). Differences in the findings at the team level of this study might be attributed to the decrease in the variability of the data when using team‐level aggregation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…No significant relationships emerged when analyzing the data at the team level, whereas at the individual level, all the hypothesized relationships were significant. The results obtained at the team level disagree with the BPNT postulates (Ryan & Deci, ), but results at the individual level are in accordance with the postulates of the theory as well as with previous research at the individual between‐person level where the needs were analyzed separately (Castillo et al., ) or together (e.g., Bartholomew et al., ; Balaguer et al., ). Differences in the findings at the team level of this study might be attributed to the decrease in the variability of the data when using team‐level aggregation.…”
Section: Discussionsupporting
confidence: 79%
“…Most of these studies have analyzed and found support for the relationships between individual perceptions of the coach's autonomy support, athletes’ basic psychological need satisfaction, and different indices of well‐ and ill‐being, through cross‐sectional (e.g., Adie et al., ) and longitudinal studies (e.g., Adie et al., ). Regarding the study of the darker side of the theory, the relationships between individual perceptions of a controlling interpersonal coaching style, athletes’ basic psychological need thwarting, and the impact on their ill‐being were also tested recently in the sport context (e.g., Castillo et al., ).…”
Section: Present Studymentioning
confidence: 99%
“…Además, en contextos de mucha presión y poco espacio para comunicar cómo se sienten o qué necesitan, los deportistas tienen menos posibilidad de encontrar vías para el desarrollo personal y social, lo cual podría incidir en la percepción de la propia competencia y de la posibilidad de generar interacciones satisfactorias con otras personas. Así, tal y como ocurre en este trabajo, existe una mayor probabilidad de dificultar la satisfacción de las necesidades psicológicas básicas (Castillo et al, 2012).…”
Section: Discussionunclassified
“…Sin embargo, el conocimiento sobre el estilo interpersonal controlador viene siendo más limitado (Bartholomew, Ntoumanis, Ryan, Bosch, y Thogerse-Ntoumani, 2011). No obstante, respecto a este último, en los diferentes ámbitos donde se ha estudiado, coinciden al apuntar en la misma línea, alertando de sus consecuencias negativas a nivel afectivo, cognitivo y comportamental para la persona (Castillo, González, Fabra, Mercé, y Balaguer, 2012).…”
Section: Introductionunclassified